Three parties, one direction: Research priorities in adults with congenital heart disease. What do professionals, patients and relatives want to know?. (15th March 2016) - Helm, Paul C.; Körten, Marc-André; Abdul-Khaliq, Hashim; Asfour, Boulos; Baumgartner, Helmut; Breithardt, Günter; Kececioglu, Deniz; Schlensak, Christian; Diller, Gerhard-Paul; Bauer, Ulrike M.M.
Abstract: Background: Patients, their relatives, as well as medical specialists from the fields of paediatric cardiology, cardiology and cardiac surgery were surveyed to investigate the current research needs in the field of congenital heart disease (CHD) focussing specifically on the needs of those affected. Material and methods: An online survey including four groups of patients with CHD (Fontan circulation, transposition of the great arteries [TGA] after atrial switch [AS] and after arterial switch operation [ASO], tetralogy of Fallot [TOF]) was performed. Each questionnaire comprised twelve topics. Persons affected (patients and relatives) were surveyed by means of CHD group specific questionnaires. Participants were recruited through the German National Register for Congenital Heart Defects. Results: N = 596 affected persons (Fontan circulation: n = 189; TGA after AS: n = 64; TGA after ASO: n = 90; TOF: n = 253) and 75 physicians (57.3% paediatric cardiologists, 28.0% cardiologists, 10.7% cardiac surgeons, 4.0% other) participated. In general, those affected assume a greater need for research than physicians. Regarding the CHD related topics to be the focus of future research, those affected largely agreed with the participating physicians, although with a different ranking of research topics. Conclusions: Based on the results of our study the challenges immanent in routine care for the CHD patient groups investigated can be identified. Accordingly, these topics should be prioritized in the research of the coming years.